Successful control of Elizabethkingia meningoseptica outbreak in a neuro-surgical intensive care unit of a tertiary care hospital in North India - Jaggi, Namita; Singh, Vyoma (International Journal of Infection Control, 2018)
Elizabethkingia meningoseptica has been found to be associated with a broad range of infectious etiologies, most notably outbreaks of neonatal meningitis. In adults, it can also cause pneumonia, endocarditis, bacteremia, meningitis and even skin and soft tissue infections, primarily in immunocompromised individuals.We report a cluster of 3 cases with E. meningoseptica infection in an adult neurology critical care unit of a 400-bedded tertiary care hospital situated in Gurugram (Delhi-National Capital Region), India.Two patients were diagnosed with ventilator-associated-pneumonia (VAP) and one was a patient in whom the organism was isolated from a cerebrospinal fluid (CSF) sample. Clinical details were studied and outbreak investigation was carried out. We found the following common risk factors for infection: Prolonged ICU stay, exposure to multiple antibiotics, presence of underlying co-morbidities and insertion of multiple invasive medical devices.E. meningoseptica was isolated from the catheter mount connected between endotracheal tube and ventilation circuit of one patient but clonality could not be studied. Strict infection control protocols and environmental cleaning procedures terminated the outbreak.